Integrative transcriptomic and metabolomic analysis reveals the molecular basis of leaf variegation in Cymbidium ensifolium - Jiang, Yu; Wang, Jin; Tu, Xuliang; Zhong, Min; Wan, Bin (Frontiers in Plant Science, 2026)
IntroductionLeaf variegation is a key ornamental trait of Cymbidium ensifolium (Jianlan); however, the molecular mechanisms underlying leaf color mutations in variegated sectors remain poorly understood. Elucidating the regulatory networks associated with pigment variation is essential for both basic research and ornamental improvement.MethodsWild-type plants and two leaf color mutants—spot variegation type (BanYi) and line variegation type (XianYi)—were analyzed. Samples were divided into five groups based on leaf origin and color: CK (wild type), B (yellow sectors of BanYi), BL (green sectors of BanYi), X (yellow sectors of XianYi), and XL (green sectors of XianYi). Integrated transcriptomic and metabolomic analyses were performed. Differential expression analysis was conducted across four comparison groups (B vs BL, B vs CK, X vs CK, and X vs XL). Co-expression analysis, metabolite profiling, correlation analysis, and weighted gene co-expression network analysis (WGCNA) were used to identify key regulatory genes and modules associated with pigment accumulation.ResultsA total of 6,716 differentially expressed genes (DEGs) were identified, with 141 shared among all comparison groups. These DEGs were significantly enriched in phenylpropanoid biosynthesis, zeatin biosynthesis, and flavonoid biosynthesis pathways. Twenty-four DEGs involved in flavonoid biosynthesis, including structural genes such as CCOAMT, TT4, and HCT, showed elevated expression in variegated leaf sectors. In addition, 80 transcription factors from the MYB, bHLH, and WRKY families were co-expressed with 50 pigment-related DEGs, suggesting coordinated transcriptional regulation. Metabolomic analysis identified 3,024 differentially accumulated metabolites (DAMs), of which 56 were shared across all groups. Correlation analysis revealed strong associations between co-DEGs and co-DAMs. WGCNA further identified key modules, including the “MEtan” module, which contained 83 genes significantly correlated with pigment-related metabolites such as 1′-Hydroxy-γ-carotene and violaxanthin.DiscussionThese results demonstrate that leaf variegation in C. ensifolium is regulated by coordinated transcriptional and metabolic networks, particularly involving flavonoid and carotenoid-related pathways. The identified structural genes, transcription factors, and co-expression modules provide novel insights into the genetic basis of leaf color variation and offer valuable candidate targets for the ornamental improvement of Jianlan.